Us kids [videorecording (DVD)] - Corin, Jaclyn; Gonzalez, Emma; Hogg, David, 2000- (Greenwich Entertainment, 2021)
Sparked by the plague of gun violence ravaging their schools, the March For Our Lives movement included Emma Gonzalez, David Hogg, Cameron Kasky, Samantha Fuentes, gun violence survivors, and teenage activists who pulled together the largest youth protest in American history. Their movement went global with rallies on six continents and in over 700 cities in every state across the nation, expanding to address racial injustice, a growing public health crisis, and shocking a political system into change. The March For Our Lives movement was instrumental in the record youth voter turnout in 2018 and 2020.